Design of Arabic Learning for Senior High School in the 21st Century - Febriani, Suci Ramadhanti; Wargadinata, Wildana; Syuhadak, Syuhadak; Ibrahim, Faisal Mahmoud Adam (Universitas Islam Negeri Raden Intan Lampung, 2020)
Arabic learningin the senior high school level still requires good planning to be able to carry out the process and evaluation of learning in accordance with the desired goals. Arabic learning in Indonesia is still focused on the delivery of material using traditional methods, only a few schools have developed the Arabic learning process in accordance with the demands of 21st century learning. It is appropriate that Arabic learning can internalize the values of soft skills in terms of cognitive, affective or psychomotor through attractive and innovative learning designs. This study aims to construct materials, media, method and evaluation that are in accordance with 21st century in Arabic language learning designs. This research method used a qualitative method based on text analysis. Therefore, the analysis used in reading and interpreting qualitative data is content analysis and system analysis. The results of this research recommend that Arabic learning designs for high school level suitable for the 21st century should contain; 1) must construct material by contextual material, 2) using technology and information, 3) using cooperative learning model based on HOTS in learning process, 4) evaluation using authentic assessment.Arabic learning in a holistic and integral way can answer the challenges of the 21st century. This paper discusses reformulate learning based on learning in the global era as an ideal alternative for Arabic learning.